Music, Mortality, Memory - Davies, Douglas; McCullough, Matthew (Death in History, Culture, and Society, 2026)
Music comes to our aid when confronted with a sense of our own mortality as here revealed in a variety of contexts and moods. Musical composition and performance significantly influence and draw from personal loss and group trauma, gaining force in kaleidoscopic patterns of shared grief; so, too, with spiritual, devotional, and ritual participation. The chapters of this book, rooted in cultural, historical, and social case studies, exemplify these musical dynamics. Alert to a variety of diverse academic disciplines, the introduction and conclusion provide additional analysis and not only indicate directions for future research, but also for contemporary study across the humanities and social sciences. Contributors are: Janieke Bruin-Mollenhorst, Jonathan Clinch, Douglas Davies, Benjamin Goodman, Thomas Graves, Erin Johnson-Williams, Daithí Kearney, Wolfgang Marx, Matthew McCullough, and Maximillian Rosenthal.